2016
DOI: 10.1186/s12879-016-1549-4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving adherence to treatment for latent tuberculosis infection: a systematic review

Abstract: BackgroundLatent tuberculosis infection (LTBI) control relies on high initiation and completion rates of preventive treatment to preclude progression to tuberculosis disease. Specific interventions may improve initiation and completion rates. The objective was to systematically review data on determinants of initiation, adherence and completion of LTBI treatment, and on interventions to improve initiation and completion.MethodsA systematic review of the literature (PubMed, Embase) published up to February 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 70 publications
4
46
0
Order By: Relevance
“…However, the 3‐ to 4‐month rifampicin regimen and the 3‐month weekly rifapentine‐plus‐isoniazid regimen had fewer hepatotoxicity events . Also, Stuurman et al found that shorter treatment regimens resulted in higher completion rates (OR = 1.92; 95% CI, 1.05‐3.52) in a meta‐analysis . These results, coupled with cost‐effectiveness data in each setting, should be used to support a stronger case for prioritizing the routine use of shorter treatment regimens for LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 3‐ to 4‐month rifampicin regimen and the 3‐month weekly rifapentine‐plus‐isoniazid regimen had fewer hepatotoxicity events . Also, Stuurman et al found that shorter treatment regimens resulted in higher completion rates (OR = 1.92; 95% CI, 1.05‐3.52) in a meta‐analysis . These results, coupled with cost‐effectiveness data in each setting, should be used to support a stronger case for prioritizing the routine use of shorter treatment regimens for LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, may affect the choice of regimen and the intensity of follow up provided to the patients when healthcare providers become aware of those at high cumulative risk of progression. Although lack of adequate healthcare as well as patient related factors have been reported to affect adherence to LTBI treatment [6, 14, 15], specific interventions like shorter duration of therapy using Rifamycin based regimens and directly observed treatment (DOT) are well recognized measures to improve treatment adherence [1618]. This approach also minimizes the loss to follow up which was the major reason for incomplete treatment in our cohort.…”
Section: Discussionmentioning
confidence: 98%
“…This is especially important as more than 85% of subjects with HIV/AIDS were prescribed INH and only 30% were able to complete treatment in our study. Current US guidelines recommend use of 3HP only with efavirenz (EFV) - or raltegravir (RAL)-based regimens (in combination with either abacavir/lamivudine [ABC/3TC] or tenofovir disoproxil fumarate/emtricitabine [TDF/FTC]) for treatment of LTBI [18]. Allowing for drug resistance testing and patient adherence factors, a future strategy of temporarily switching HIV positive patients to the above mentioned regimens could allow better treatment completion rates with a 3HP based regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of the inventory, the assessment has continued and a series of systematic literature reviews has been performed [9-14]. The next step will be to conduct mathematical modelling and cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%